FACTORS THAT INFLUENCE THE OCCURENCE OF ANEMIA IN PREGNANT WOMEN AT PMB ROHANA JAMBI PROVINCE IN 2023 - Anis Lestari; Ernamari; Nurmalina Hutahaean, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Title: factors that influence the occurrence of anemia in pregnant women at PMB Rohana Jambi Province in 2023. Background: anemia is a condition when the number of red blood cells or oxygen- transporting concentrations (Hb) is insufficient for the physiological needs of the body. While the effects of anemia on pregnancy include miscarriage, premature labor, bleeding shock, inpartum infection and if anemia in Hb is less than 4%, heart trouble not only complicates pregnancy and childbirth, it can even break. Kuragny maternal knowledge about anemia in this study is due to the influencing factors such as: knowledge, age, education and employment of the mother. The purpose of this study is " factors that influence the occurrence of anemia in pregnant women at PMB Rohana Jambi Province in 2023 " Method: This type of research is a research design that is used in this research is analytic with a cross sectional approach. Samples in the study were taken by total sampling, amounting to 34 respondents. Data collection using questionnaires and check lists. The data analysis used was univariate analysis with percentage and bivariate analysis using Chi-Square test Results: The results of the study, the incidence of anemia was 58.8%, the majority had less knowledge of 50.00%, those who had <20 years old, the majority was 52.9%, those who had junior high school education, the majority were 11 32.4%, majority of 15 IRT jobs are 44.1%. The bivariate analysis concluded that there was a relationship between knowledge, education age, occupation and anemia in pregnant women at the PMB Rohana Jambi Province in 2023. (p-value 0.002%) Conclusion: from the study it can be concluded that there is a relationship between knowledge, age, work education and anemia in pregnant women